1934
DOI: 10.1063/1.1749444
|View full text |Cite
|
Sign up to set email alerts
|

An X-Ray Study of the Structure of Liquid Benzene, Cyclohexane and Their Mixtures

Abstract: Carefully purified benzene and cyclohexane exhibit x-ray diffraction peaks corresponding to preferred spacings of 4.68A and 5.09A, respectively, which are interpreted as the effective thicknesses of the respective rings. Mixtures of these two hydrocarbons give rise to two independent diffraction peaks indicating emulsion-type solutions, in which the disperse phase is too small to show even a Tyndall effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1937
1937
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…From self-diffusion measurements it was only concluded that there are aggregates of molecules present in these solutions [ 72 ]. On the other hand, Ward interpreted the X-ray diffraction results in terms of formation of an emulsion-type solution, in which the disperse phase is too small to manifest a Tyndall effect [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…From self-diffusion measurements it was only concluded that there are aggregates of molecules present in these solutions [ 72 ]. On the other hand, Ward interpreted the X-ray diffraction results in terms of formation of an emulsion-type solution, in which the disperse phase is too small to manifest a Tyndall effect [ 73 ].…”
Section: Resultsmentioning
confidence: 99%